(untitled) (Global Journal of Human-Social Science, 2021)
This is a theoretical article on neoliberalism in the 21st century, which aims to articulate the notion of neoliberal rationality with Karl Polanyi’s concept of "satanic mill". Based on the analysis of the historical shaping of neoliberalism in Brazil and in world, on the approaches of Brazilian political thought and, at the international level, supported by Christian Laval, Pierre Dardot, Wendy Brown and Nancy Fraser, I defend the argument that the neoliberal reason, similar to liberalism in the Industrial Revolution period, is a mechanism that destroys social tissues, promotes competition in all dimensions of human life and authoritarian forms of politicalsocial organization.